Adoption of National Roadmap to Urban Food Waste Prevention and Reduction in Households, Food Services, Retailers and Wholesalers, Sri Lanka - CGIAR Research Program on Water, Land and Ecosystems (2021)
A research-based strategy to reduce food waste and recycle it is adopted by the government.